Biomimetic porous collagen/hydroxyapatite scaffold for bone tissue engineering. Issue 37 (5th June 2017) - Chen, Li; Wu, Zhenxu; Zhou, Yulai; Li, Linlong; Wang, Yu; Wang, Zongliang; Chen, Yue; Zhang, Peibiao
ABSTRACT: Bone defect and osteochondral injury frequently occur due to diseases or traumatism and bring a crucial challenge in orthopedics. The hybrid scaffold has shown promise as a potential strategy for the treatment of such defects. In this study, a novel biomimetic porous collagen (Col)/hydroxyapatite (HA) scaffold was fabricated through assembling layers of Col containing gradual amount of HA under the assistance of "iterative layering" freeze‐drying process. The scaffold presents a double gradient of highly interconnected porosity and HA content from top to bottom, mimicking the inherent physiological structure of bone. Owing to the biomimetic structure and component, significant increase of cell proliferation, alkaline phosphatase activity, and osteogenic differentiation in vitro was observed, illustrating potential application of the excellent Col/HA scaffold as a promising strategy for bone tissue engineering. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45271. Abstract :